Hybrid Dispute Resolution in Administrative Law: Toward an Integrated Model for Government Conflict Management - Subrata, Rusli; Arifin, Firdaus; Maarif, Ihsanul (Universitas Internasional Batam, 2025)
The increasing complexity of citizen–government interactions in administrative law has revealed the limitations of litigation-based dispute resolution, which is often criticized for its rigidity, inefficiency, and lack of procedural inclusiveness. This study aimed to develop a conceptual model of Hybrid Dispute Resolution (HDR) that integrates judicial procedures with alternative dispute resolution (ADR) mechanisms to enhance fairness, participation, and institutional responsiveness in resolving administrative disputes. A normative juridical method was employed, incorporating statutory, conceptual, and comparative approaches. Legal frameworks and institutional practices in Singapore, China, and Poland were examined to identify key elements for HDR adaptation within the context of Indonesian administrative law. These findings indicate that HDR, particularly through models such as Med-Arb and Arb-Med, can effectively combine the legal certainty of litigation with the flexibility and participatory benefits of ADR. However, successful implementation requires a robust legal framework, trained mediators, institutional readiness, and public accountability mechanisms. HDR not only provides procedural alternatives but also contributes to the democratization of public administration by enabling citizens to directly engage with the state in resolving disputes. This reflects a paradigm shift toward more adaptive and humanistic governance. The HDR offers a viable framework for reforming administrative dispute resolution systems, with broad implications for access to justice, regulatory innovation, and the enhancement of citizen–state relations in democratic governance.